Crystal structure of a G:T/U mismatch-specific DNA glycosylase: mismatch recognition by complementary-strand interactions. - Barrett, T; Savva, R; Panayotou, G; Barlow, T; Brown, T; Jiricny, J; Pearl, L (1998)
G:U mismatches resulting from deamination of cytosine are the most common promutagenic lesions occurring in DNA. Uracil is removed in a base-excision repair pathway by uracil DNA-glycosylase (UDG), which excises uracil from both single- and double-stranded DNA. Recently, a biochemically distinct family of DNA repair enzymes has been identified, which excises both uracil and thymine, but only from mispairs with guanine. Crystal structures of the mismatch-specific uracil DNA-glycosylase (MUG) from E. coli, and of a DNA complex, reveal a remarkable structural and functional homology to UDGs despite low sequence identity. Details of the MUG structure explain its thymine DNA-glycosylase activity and the specificity for G:U/T mispairs, which derives from direct recognition of guanine on the complementary strand.